Sovereign liquidity crises: Analytics and implications for public policy - Chui, Michael; Gai, Prasanna; Haldane, Andrew G (Journal of Banking & Finance, 2002)
This paper offers an analytical framework with which to assess some recent proposals for strengthening the international financial architecture. We develop a model of sovereign liquidity crises that reflects two sources of financial stress – weak fundamentals and self-fulfilling expectations. We examine the nature of the underlying co-ordination game and investigate the properties of the unique equilibrium. In so doing, we are able to characterise the welfare costs of belief-driven crises, which we find to be potentially significant. We also evaluate some recent policy proposals including prudent debt and liquidity management, capital controls, greater information disclosure, and the efficacy of monetary policy tightening in the midst of crisis.